2020
DOI: 10.1111/ajt.15686
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood bicarbonate and pH with mineral metabolism disturbance and outcome after kidney transplantation

Abstract: In kidney transplant recipients (KTRs), scarce evidence has associated low blood bicarbonate levels with mineral metabolic disturbance and reduced allograft survival. However, the contribution of the blood pH to these observations remains unassessed. Equally, little is known about the influence of the blood provenance (arteriovenous fistula vs peripheral vein) on bicarbonate values. We analyzed blood gas parameters in a single‐center cohort of 1260 stable KTRs, 3 months after transplantation. Inspection of pO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…Five studies found a higher percentage or an association of MA in KTRs after deceased donor KTx [4,[22][23][24]58], while in three other studies, no association was found for donor type [41,49,58,59]. Only one study reported on prolonged cold ischemia time and an association with MA 3 months after transplantation [24]. So far, no association with donor age [22,24] or sex was identified [22].…”
Section: Donation and Donormentioning
confidence: 92%
See 4 more Smart Citations
“…Five studies found a higher percentage or an association of MA in KTRs after deceased donor KTx [4,[22][23][24]58], while in three other studies, no association was found for donor type [41,49,58,59]. Only one study reported on prolonged cold ischemia time and an association with MA 3 months after transplantation [24]. So far, no association with donor age [22,24] or sex was identified [22].…”
Section: Donation and Donormentioning
confidence: 92%
“…Since the 1980s, CNIs are a key component of long-term immunosuppressive regimen after organ transplantation. Several studies could demonstrate an association of CNIs with the occurrence of chronic MA, with some evidence that it occurs more frequently with tacrolimus than cyclosporine A [22,24,41,47,48]. This effect seems to be dose dependent [49,50].…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations